Effect of Interleukin-15 on CD11b, CD54, and CD62L Expression on Natural Killer Cell and Natural Killer T-Like Cells in Systemic Lupus Erythematosus - Syh-Jae Lin; Ji-Yih Chen; Ming-Ling Kuo; Hsiu-Shan Hsiao; Pei-Tzu Lee; Jing-Long Huang (Mediators of Inflammation)
Adhesion molecules may play an important role in systemic lupus erythematosus (SLE) pathogenesis. We investigated the effect of interleukin- (IL-) 15 on CD11b, CD54, and CD62L expression on natural killer (NK) cells, T cells, and CD56+CD3+ NKT-like cells from SLE subjects and healthy controls. SLE patients had decreased circulating NK cells and NKT-like cells compared to controls. NK cells from SLE patients showed higher CD11b and CD62L expression compared to controls. IL-15 enhanced CD11b and CD54 but downregulated CD62L expression on NK cells from SLE patients. Similar observations were found for T cells and NKT-like cells. NK cells from SLE patients expressed higher CD56 than controls; both could be further enhanced by IL-15. IL-15 also enhanced CD56 expression of NKT-like cells from SLE patients. A greater degree of IL-15 induced downregulation of CD62L on NKT-like cells noted in SLE patients compared to controls. The percentage of CD11b expressing NK cells and the % inhibition of CD62L expression on NKT-like cells by IL-15 correlated with serum anti-dsDNA levels in SLE patients, respectively. Taken together, we demonstrated the dysfunctional NK and NKT-like cells in SLE patients with regard to CD11b and CD62L expression and their response to IL-15.